2018
DOI: 10.1039/c8cc04962a
|View full text |Cite
|
Sign up to set email alerts
|

Disilanylene-bridged BODIPY-based D–σ–A architectures: a novel promising series of NLO chromophores

Abstract: The synthesis and optical properties of a novel series of disilanylene-bridged BODIPY-based D-σ-A chromophores are reported. Si-Si σ-electrons are useful and impressible for tunable optical properties. The electron-donating group facilitates enhancement of the CT nature of the excited state through σ(Si-Si) orbital, leading to the remarkable two-photon absorption cross-sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Two different conformations of BTPE-Sin (n = 2-4) are possible, viz, folded and extended structures. 10 Density functional theory (DFT) calculations showed that the folded conformation of BTPE-Si2 was more stable than its extended structure (Supporting Information Figure S11), which is consistent with the single-crystal structure analysis, obtained by X-ray diffraction using the process of slow dichloromethane/acetonitrile liquid phase diffusion for crystal growth ( Figure 5). The torsion angle of the phenyl-Si-Si-phenyl moiety is ∼ 58°, which indicated that BTPE-Si2 adopted a distorted conformation in crystals, without apparent C-H : : : π or π : : : π interactions.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Two different conformations of BTPE-Sin (n = 2-4) are possible, viz, folded and extended structures. 10 Density functional theory (DFT) calculations showed that the folded conformation of BTPE-Si2 was more stable than its extended structure (Supporting Information Figure S11), which is consistent with the single-crystal structure analysis, obtained by X-ray diffraction using the process of slow dichloromethane/acetonitrile liquid phase diffusion for crystal growth ( Figure 5). The torsion angle of the phenyl-Si-Si-phenyl moiety is ∼ 58°, which indicated that BTPE-Si2 adopted a distorted conformation in crystals, without apparent C-H : : : π or π : : : π interactions.…”
Section: Resultssupporting
confidence: 81%
“…4 The oligosilanyl linkages allowed their functionality to be manipulated by an efficient σ-π conjugation between Si-Si σ-orbitals and aryl π-orbitals. [5][6][7][8][9] Also, the large atomic radius of silicon (Si) and the bulk of the organosilicon linkage aided in improving the solubility and processability effectively, 10 which is beneficial for the practical applications of these materials. [11][12][13][14] Red-, green-, and blue-emissive organic materials are required to realize full-color displays.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation of these compounds at their respective maximum absorption wavelength at room temperature resulted in the same near‐infrared emissive BODIPY dyes with emission maxima of 669, 678 and 677 nm, respectively. This can be explained that there is a thorough intermolecular energy transfer of the excitons from the BODIPY core to the donor unit at the π‐conjugated system . The results also imply that on the basis of intramolecular energy transfer from the BODIPY π‐π* excited state to the lower lying singlet excited state of the donor moieties and/or to the existence of new non‐radiative pathways from the BODIPY π‐π* excited state to the ground state .…”
Section: Resultsmentioning
confidence: 99%
“…ESA from the S 1 or T 1 state can result in an RSA response when the ESA is more intense than the ground state absorbance, due to the effect of depopulating the ground state (Saleh and Teich, 1991; Tutt and Boggess, 1993; de la Torre et al, 2004), so only a β eff value can be quantified for the non-linear absorption coefficient rather than the intrinsic β value that is associated with 2PA. There have been a limited number of studies of the intrinsic β values of BODIPY dyes in femtosecond pump-probe studies (Wang et al, 2010; Kim et al, 2015; Zheng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular dyes that have been used as optical limiters typically have a delocalized π-conjugation system which is highly polarizable when interacting with intense laser light (Kandasamy et al, 1997; Ogawa et al, 2002; de la Torre et al, 2004). Phthalocyanines and porphyrins have been the main compounds of interest in this context (Calvete et al, 2004; Chen et al, 2005; Senge et al, 2007), while until recently there had been relatively little research reported on boron-dipyrromethene (BODIPY) dyes in this context (Zhu et al, 2008; Zheng et al, 2009, 2018; Frenette et al, 2014; Kulyk et al, 2016, 2017; Thakare, 2017). Over the past 2 years, we have demonstrated that 3,5-distyrylBODIPY dyes exhibit strong OL responses on the nanosecond timescale (Ndebele et al, 2019).…”
Section: Introductionmentioning
confidence: 99%